The risk for delayed development in low birth weight, appropriate for gestational age preterm infants - Stanza Uga Peryoga; Abdurachman Sukadi; Sambas Wiradisuria (Indonesian Pediatric Society Publishing House, 2016)
Background Preterm infants, particularly those who have had severe asphyxia, hyperbilirubinemia, and sepsis, tend to be at risk for neurodevelopmental impairment. Objective The purpose of this study was to assess the risk for de- layed development in low birth weight (LBW), appropriate for gesta- tional age (AGA) preterm infants compared to that in term, non-LBW infants, and to investigate the roles of severe asphyxia, sepsis, and hyperbilirubinemia as potential risk factors for delayed development. Methods This was a hospital-based retrospective cohort study involving preterm, LBW and term, non-LBW infants conducted in Hasan Sadikin Hospital, Bandung. The Bayley Infant Neurodevelopmental Screener (BINS) test was performed to as- sess the risk of delayed development at 3 months of corrected age for the preterm infants and at 3 months of chronological age for the term infants. Bivariate analysis using the chi-square test and mul- tivariate analysis using logistic regression were performed. Results One hundred and twelve infants fulfilled eligibility criteria, consisting of 52 preterm, LBW and 60 term, non-LBW infants. Based on the BINS test, of the preterm, LBW infants, 32 (61%) were at low risk, 11 (21%) at moderate risk, and 9 (17%) at high risk for delayed development. Of the control infants, 49 (82%) were at low risk, 10 (17%) at moderate risk, and 1 (1.7%) at high risk for de- layed development. Logistic regression analysis showed signifi- cant association between accompanying diseases such as sepsis (OR=25.60; P=0.001) and hyperbilirubinemia (OR=16.07; P=0.001) with delayed development. Despite more than twofold odds for delayed development in infants with severe asphyxia (OR=2.51) and LBW-prematurity (OR=2.47), the association was statistically insignificant (P=0.20 and P=0.15, respectively). Conclusions In preterm infants appropriate for gestational age, prematurity and low birth weight alone may or may not predispose to delayed development at 3 months of age. However, the risk for delayed development in such infants is increased when sepsis or hyperbilirubinemia is present